Analisis Proses Kognitif Siswa dalam Mengerjakan Soal Cerita Matematika Berdasarkan Taksonomi Bloom pada Materi SPLDV Kelas X SMAN 1 Kota Tambolaka - Peha, Samuel Dadi; Napu, Timotius Woda; Lede, Yulius Keremata; Making, Samuel Rex Mulyadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Students' ability in solving mathematical word problems, especially in the Two-Variable Linear Equation System (SLS), is still relatively low because many students have difficulty in understanding the context of the problem, determining the solution strategy, and developing higher-order thinking skills. This study aims to analyze the cognitive processes of class X B students of SMA Negeri 1 Kota Tambolaka in solving SLS story problems based on Bloom's Taxonomy. The study used a descriptive qualitative approach involving 23 students as test participants, then six students were selected by purposive sampling to be interviewed representing the high, medium, and low ability categories. Data were collected through written tests, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model with triangulation as a test of data validity. The results showed that high-ability students were able to reach all levels of cognitive processes (C1–C6), medium-ability students reached C1–C4 but still experienced difficulties in C5 and C6, while low-ability students only reached C1–C3 and were not yet able to perform analysis, evaluation, and creation adequately. These findings indicate that students' higher-order thinking skills have not developed evenly, so teachers need to design learning and assessments that gradually train analytical, evaluation, and creative skills in solving mathematical story problems.